2022
DOI: 10.3390/su141912526
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Thermal Comfort and Air Quality of Room Conditions by Impinging Jet Ventilation Integrated with Ductless Personalized Ventilation

Abstract: Advanced ventilation methods are responsible for creating an appropriate temperature environment with satisfactory inhaled air quality. The ductless personalized ventilation system integrated with impinging jet ventilation shows the good ventilation performance. In order to investigate the effect of using such an integrated system on thermal comfort and air quality improvement. Twenty subjects participated in a chamber test at 25 °C, 27 °C, and 29 °C, respectively, with operating DPV devices at three modes (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…As shown in Fig. 11(b), all nine experimental conditions exist for subjects who want the thermal environment to become colder or warmer, indicating that subjects' thermal preferences differ [63]. The voting results for those who want the thermal environment to become warmer account for approximately 57% (two occupants) and 43% (four occupants), under the baseline control strategy.…”
Section: Thermal Acceptability and Thermal Preferencementioning
confidence: 93%
“…As shown in Fig. 11(b), all nine experimental conditions exist for subjects who want the thermal environment to become colder or warmer, indicating that subjects' thermal preferences differ [63]. The voting results for those who want the thermal environment to become warmer account for approximately 57% (two occupants) and 43% (four occupants), under the baseline control strategy.…”
Section: Thermal Acceptability and Thermal Preferencementioning
confidence: 93%
“…Personalized ventilation systems offer a solution by allowing individuals to control their immediate microenvironment, adjusting airflow and temperature to their specific needs. This tailored approach can reduce the risk of discomfort [4] and health issues associated with poor air quality, such as headaches, dry eyes, and respiratory problems [5]. Studies have shown that providing employees with the ability to customize their ventilation can lead to significant improvements in cognitive function, concentration, and overall job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The high-velocity airflow is discharged downwards and strikes the floor, forming a thin layer of airflow that spreads in all directions. Thermal stratification occurs when the cool air layer is heated by indoor heat sources [6].…”
Section: Introductionmentioning
confidence: 99%